Different presentation of autoimmune hepatitis in children: Case series - Qudsiya Ansari; Vishal Sawant; Alpana Santosh Kondekar (Journal of Family Medicine and Primary Care)
Autoimmune hepatitis (AIH) is a disorder causing chronic hepatic inflammation. Its clinical presentation is highly variable from the affected child might have only biochemical evidence of liver dysfunction or present in hepatic failure. It is important to distinguish AIH from other forms of chronic hepatitis because a high percentage of cases respond to immunosuppressive therapy. In this article, we describe the clinical presentation, biochemical and histological findings, treatment, and clinical outcome of the four children with AIH in a tertiary care center in Mumbai. Most patients with AIH have high levels of immunoglobulin. All four cases showed high serum Ig G levels and responded to oral prednisolone only. AIH should be excluded for all patients with symptoms or signs of prolonged, relapsing, or severe liver disease so that treatment can be promptly initiated and morbidity can be reduced.